(untitled) (SAARC Journal of Agriculture, 2025)
Sheep farming is gaining popularity nowadays; however, its expansion is being restricted by numerous diseases and disorders. The study aimed to assess sheep disease prevalence, trends and apply preventive measures. From January 2018 to December 2021, a study was conducted among sheep farmers in Companiganj and Subarnachar Upazilas of Noakhali, Bangladesh. Clinical records and disease diagnoses have been made based on pertinent clinical history, observations, and relevant tests performed in laboratories. Data were analyzed using MS Excel 2018 and SPSS 26.0. Sheep diseases were categorized by cause, year, sex, age, and season. Diarrhea (19.94%), gastrointestinal (GI) parasitic infections (15.98%), pneumonia (14.97%), alopecia (13.86%), mastitis (7.15%), dermatitis (6.71%), and enterotoxemia (5.74%) were the most frequently observed clinical conditions. Subarnachar exhibited a higher disease prevalence (53.59%) compared to Companiganj (46.41%). Sheep diseases were most common in winter (38.74%), followed by the rainy (34.38%) and summer (26.88%) seasons. Growing sheep had higher disease rates than lambs (31.28%) and adults (27.09%). Finally, the prevalence rate of female sheep was significantly higher (73.16%) than that of male sheep (26.84%), as indicated by the statistical analysis (p<0.05). These findings suggest that appropriate preventative efforts are needed to prevent these diseases and their consequences. SAARC J. Agric., 23(1): 111-122 (2025)